Pengaruh Regulasi Diri Terhadap Kenakalan Remaja di SMK Negeri 1 Sidoarjo: The Effect of Self-Regulation on Juvenile Delinquency in Vocational Schools State 1 Sidoarjo - Okta Cintiya Putri; Eko Hardi Ansyah (Academia Open, 2025)
General Background: Adolescence is a transitional developmental phase characterized by biological, cognitive, and socio-emotional changes that may lead to maladaptive behaviors such as juvenile delinquency. Specific Background: At SMK Negeri 1 Sidoarjo, various forms of misconduct including truancy, dishonesty, and rule violations have been reported, indicating behavioral regulation concerns among vocational students. Knowledge Gap: Although previous studies have linked self-regulation to delinquent behavior, empirical evidence within vocational school contexts remains limited. Aims: This study aims to examine the relationship between self-regulation and juvenile delinquency among students of SMK Negeri 1 Sidoarjo. Results: Using a quantitative regression design with 250 students selected through purposive sampling, findings revealed a significant negative association between self-regulation and juvenile delinquency (β = -0.561, p < 0.05), indicating that higher self-regulation corresponds with lower levels of delinquent behavior. Novelty: This research provides contextual empirical data from a vocational school population, highlighting the central role of self-regulation in adolescent behavioral outcomes. Implications: Strengthening self-regulation through school-based programs and structured student activities may contribute to reducing misconduct and supporting positive developmental trajectories among vocational students. Keywords: Self Regulation, Juvenile Delinquency, Vocational Students, Adolescence, Quantitative Regression Key Findings Highlights: Most students demonstrated moderate levels of behavioral control and misconduct tendencies. Negative beta coefficient indicates inverse association between the two variables. Strengthening internal control mechanisms may reduce rule-violating behaviors in school settings.